ANALISIS KUALITAS LAYANAN PENDIDIKAN DENGAN MENGGUNAKAN INTEGRASI METODE SERVQUAL DAN QFD: STUDI KASUS SEKOLAH YASPORBI - Deny Wibisono (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
The application of quality management education that is popular with the term Total Quality Education (TQE) emphasis on finding that is consistent with the continuous improvement to achieve customer needs and satisfaction. This study aims to assist the school management in evaluating the quality of services, direct remediation efforts to improve service attributes weak. The study was conducted in SMA YASPORBI by integrating two different methods, namely SERVQUAL and QFD. Servqual identify the strengths and weaknesses of the quality of service, QFD translates into a customer's desire to do a technical response by the management of the school. Obtained as many as 11 educational service attributes that should be fixed on the 32 attributes of existing educational services with two attributes is a priority repairs, which teachers help students choose college majors that fit their talents and interests of students and their training in dealing with the selection of new admissions. In the House of Quality Level 2 obtained four technical response to the priorities to be developed by the school management to meet the wants and needs of customers, namely training, workshops, and educational seminars, and school linkages with institutes of psychology, learning systems moving class, and compiled a book program of activities for the school year.